Effective data management is a game changer for smallholder sheep and goat breeding programs - Getachew, Tesfaye (International Center for Agricultural Research in the Dry Areas, 2025)
In Ethiopia, an innovative and easy-to-use digital tool (DTREO) has helped Community-Based Breeding Programs (CBBPs) transform the lives of thousands of goat and sheep breeders through data collection that supports more informed decisions on selecting superior males for breeding and access to new market opportunities. DTREO is now being introduced and pilot-tested by ICARDA to establish and optimize management as well as sheep and goat breeding programs in Jordan, Tunisia, and Mali.